Size fractionation by slalom chromatography and hydrodynamic chromatography - Dias, Ricardo P. (2008)
Hydrodynamic chromatography, also called separation by flow, is based on the use of the parabolic flow profile occurring in open capillaries or in the pores from a column filled with non-porous particles. The hydrodynamic chromatography separation medium, if any, is much simpler than that from size exclusion chromatography (porous particles), the former technique being used in the size-fractionation of many colloids and macromolecules. The transition between hydrodynamic chromatography (obtained using low flow rates) and slalom chromatography (obtained using high flow rates) was reported in studies related with the migration behaviour of proteins, plasmid DNAs and double stranded DNAs. Slalom chromatography is mainly applied in the size-fractionation of large double stranded DNA fragments and may compete with electrophoretic techniques. In the present paper it is discussed the main patents, applications, advantages and drawbacks related to hydrodynamic chromatography and slalom chromatography, as well as some strategies that may improve the performance of these simple size-fractionation techniques.